Elective Cesarean Section for Preterm Fetuses in Vertex Presentation: Is It Effective to Improve The Neonatal Outcomes? - Altay Gezer; Mahmut Öncül; Orçun Koçak; Sanlı Erkan; Seyfettin Uludağ; Tarık Altınok (Medical Network, 2006)
OBJECTIVE: Evaluation of the assumption that elective cesarean section (CS) improved neonatal outcomes of 'preterm fetuses in vertex presentation'. STUDY DESIGN: Birth records of a university hospital between 1999 and 2004 were reviewed. CS performed without a trial of labor before completion of 37 gestational weeks were included in the study group. Early neonatal and maternal outcomes were compared for the elective CS and vaginal birth groups. RESULTS: 61 elective CS and 117 preterm vaginal deliveries were eligible for the analysis. Neither the rate of NICU admission (38% v ersus 33%) nor the neonatal mortality rate (3.3% versus 4.3%) differed significantly. There were 2 cases of maternal morbidity in the CS group but none in the vaginal birth group. CONCLUSIONS: Data in this study did not demonstrate any beneficial effect of elective CS for the early neonatal outcome of preterm fetuses in vertex resentation despite the possible increase in maternal morbidity.